Effect of Diabetic Gymnastics on Blood Glucose Levels in Diabetes Mellitus Patients at Patilanggio Public Health Center - Sujani, Aceng Anwar; Djamaluddin, Nurdiana; Liputo, Gusti Pandi; Hadjarati, Hartono (Medical and Health Journal, 2025)
Diabetes is a chronic metabolic disease that, if not managed properly, will increase the occurrence of complications. The risk of disease complications can be exacerbated by the non-compliance of DM patients in controlling blood sugar, so intervention is needed in controlling blood sugar in the form of diabetic gymnastics intervention. This research used a quantitative design with the Quasi Experiment method including a Pretest-Posttest Control Group design. The population was all people suffering from type II DM without complications, and the sampling technique used was the Simple Random Sampling technique with a total of 59 samples. The instrument consisted of the questionnaire and paired t-test, obtained a value of 0.043 (<0.05) in the intervention group, which means that there is an effect of diabetic gymnastics on reducing blood sugar levels during diabetes mellitus patients in the work area of the UPTD Puskesmas Patilanggio Subdistrict, Puhuwato Regency, and 0.161 (>0.05) in the control group which means there is no effect of it. Puskesmas can use this research in preventive efforts through diabetic gymnastics and as a source of information for patients to maintain diabetes control.